(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
In today’s Indian society, especially the women of the city society, have started the effort to search for and protect their identity in a very strong way. Women have tried to create a separate individual and existence of her own. Today’s woman is playing a unique role in the progress of the society and the nation by changing from helpless woman to a strong one. Being financially independent, she is denying the shadow of man to maintain her independent existence. She has neither the desire nor the need of men today. In fact, the responsibility of leading a woman towards advancement should be that of her as well as the family and the society. Women have also played an important role in the all-round development of Indian society after independence. Before independence, Mahatma Gandhi tried his best to ensure complete freedom to the exploited, the oppressed and the oppressed women of the society and their universal development. On the call of Gandhiji, the then women also came out to sacrifice everything. Instilling awareness among women, he encouraged them to come out of the inferior gland of traditional customs and encouraged to lead a dignified and respected life. As a result, there was a strong desire among women to identify themselves as a strong and powerful human being. Mohan Rakesh is famous playwright of Indian literature. Here, on the basis of Mohan Rakesh’s dramas, the social, political, educational and economic aspect of Indian women’s identity has been highlighted.